2008
DOI: 10.21273/jashs.133.3.341
|View full text |Cite
|
Sign up to set email alerts
|

‘Kardinal’ Rose Exhibits Growth Plasticity and Enhanced Nutrient Absorption Kinetics Following Nitrate, Phosphate, and Potassium Deprivation

Abstract: Plant internal nutrient status is known to influence the kinetics of nutrient absorption, but little on this relationship has been reported for roses (Rosa spp. L.). The objectives of this experiment were to determine the influence of NO3, PO4, and K deprivation on plant tissue concentrations and relative growth rates and to quantify the influence of nutrient deprivation on absorption kinetic parameters. Rose plants growing in solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Tolley-Henry and Raper (1986) reported that N deficiency reduced shoot:root ratio in soybean (Glycine max L.) grown for 25 d in Ndeficient hydroponic solution; however, Boussadia et al (2010) reported no effect on shoot:root ratio in two hydroponically grown olive (Olea europaea L.) cultivars after 58 d of N deficiency. Our results, in conjunction with those of Boussadia et al (2010), Mattson andLieth (2008), andTolley-Henry andRaper (1986), suggest that growth in the shorter production cycles of herbaceous plants is more sensitive to N deprivation than growth in relatively longer production cycles of woody plants.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Tolley-Henry and Raper (1986) reported that N deficiency reduced shoot:root ratio in soybean (Glycine max L.) grown for 25 d in Ndeficient hydroponic solution; however, Boussadia et al (2010) reported no effect on shoot:root ratio in two hydroponically grown olive (Olea europaea L.) cultivars after 58 d of N deficiency. Our results, in conjunction with those of Boussadia et al (2010), Mattson andLieth (2008), andTolley-Henry andRaper (1986), suggest that growth in the shorter production cycles of herbaceous plants is more sensitive to N deprivation than growth in relatively longer production cycles of woody plants.…”
Section: Resultssupporting
confidence: 71%
“…Shoot mass followed a trend similar to root mass, decreasing with increasing time of N deprivation with over 67% reduction of shoot mass for plants grown without N for 26 d. Although foliar chlorophyll and N concentration recovered from longer periods in N growth solution, geranium growth was reduced and failed to completely recover for any plant receiving more than 2 d of N-free solution. Mattson and Lieth (2008) showed that rose (Rosa spp.) was not reduced in growth after 20 d of N-free solution.…”
Section: Resultsmentioning
confidence: 99%
“…where V is the solution volume, V S is the sample volume, and C is the concentration at time, t (Mattson and Lieth, 2008). Uptake of each nutrient was calculated on a total plant fresh weight (FW) basis (units of µmol h -1 g -1 FW).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…As new flower shoots reach maturity and become net exporters of carbohydrates, the root system recovers as does N uptake. Nutrient demand also depends on several other parameters including: cultivar (Kelly et al, 2000;Sharifi and Zebarth, 2006;Teo et al, 1992), environmental conditions (Wheeler et al, 1998), the nutritional history of the plant (Mattson and Lieth, 2008a;Subasinghe, 2006;Wheeler et al, 1998), and plant health as affected by abiotic and biotic stresses (Walters and Ayres, 1980). A 4-fold difference in the maximum rate of nitrate (NO 3 ) accumulation by roots was noted between cultivars of red maple (Acer rubrum) seedlings grown under the same conditions (Kelly et al, 2000).…”
Section: Factors That Affect Timing Of Plant Nutrient Demandmentioning
confidence: 99%
“…Wheeler et al (1998) found that growing lettuce plants under varying light levels and NO 3 concentrations affected relative growth rate, which in turn affected plant nutrient demand. Rose plants deprived of N, phosphorus (P), or potassium (K) for up to 20 d exhibited increased absorption of the specific nutrient that was lacking as compared with control plants that had been provided with sufficient nutrients (Mattson and Lieth, 2008a). For N and P, deprived plants showed a 2-fold increase in uptake rates when those nutrients were subsequently introduced as compared with control plants; K deprived plants showed an enhanced affinity for absorbing K at low concentrations.…”
Section: Factors That Affect Timing Of Plant Nutrient Demandmentioning
confidence: 99%